Karakteristik Snack Bar Kombinasi Tepung Jawawut (Setaria italica L. P. Beauv.) dan Tepung Garut (Maranta Arundinacae L.) - Qonitah Setiajulihana; Diah Kartikawati; Bambang Hermanu (Universitas 17 Agustus 1945 Semarang, 2024)
Snack bar is a stick-shaped snack made from flour, seeds and nuts. This research aims to determine snack bar products made from a mixture of millet flour ad arrowroot flour with the addition of walnuts, including physical properties (L*a*b* color values), chemical properties (water, ash, fat, protein and crude fiber contents), and sensory properties based on hedonic test. This study was experimental using Complete Randomized Design (CRD) with the percentage ratio treatments of millet flour and arrowroot flour consisting of formula S1 ((20%:80%); S2(30%:70%); S3(40%:60%); and S4(50%:50%). The data obtained were processed using the Variance Analysis with a confidence level of 95% (α=0,05), and Duncan’s follow-up test. Snack bars have color values L* 41,660-52,580; color a* 6,6317-9,0667; color b* 19,9017-23,9667. The results of proximate analysis showed that snack bars contains 13,7176-17,8433 of water; 0,8459-1,4455% of ash; 5,8175-7,3264% of protein; 20,5320-24,2649% of fat; 48,7558-50,1120%; and 3,6339-5,1826% of crude fiber. Millet flour increases ash and protein content, but fat and crude fiber content decrease. Based on the hedonic test, it is known that panelists liked the taste and texture of S4 snack bar with an average score 3,94 and 3,68; while for the aroma in the treatment of S3 snack bar with an average score of 3,97 and the color in the treatment of S2 snack bar with an average score of 3,97 (hedonic test scale 1=very dislike, 2=dislike, 3=neutral, 4=like, 5=very like). Snack bars combination 30% millet flour:70% arrowroot flour have the best chemical characteristics (value 1,167) and the best sensory characteristics on snack bars from combination of 50% millet four:50% arrowroot flour (value 0,745) based on the DeGarmo effectiveness index test.